Media qualities and preferences in da’wah among Muslim converts in Borneo - Salina Yanti Salim (Pusat Kesejahteraan Insan dan Komuniti, Universiti Kebangsaan Malaysia, 2021)
In line with the growth of technology, media respectively has certain qualities that attract the audience or user to preferably utilise one platform over the other. This study aims to investigate media qualities that influenced the preferences of Muslim converts in da’wah in Borneo, specifically in Sabah, Sarawak and Brunei. The media involved were of traditional media such as television, radio, book and newspaper, and of social media such as Facebook, YouTube, website and blog. The qualitative research methodology was employed and a semi-structured interview was applied to collect the data from the informant. There were 27 Muslim converts who participated in this study as informants. The data obtained from the interview was tabulated using thematic approach, which later analysed using descriptive and interpretive phenomenology approach. The results revealed that Sabah informants were more focused on technical and interactive features of media for variety of information related to da’wah, thus they preferred social media, including older informants. Meanwhile Sarawak and Brunei informants were more focused on the reliability of the da’wah content in media, thus they mostly preferred traditional media, including young informants in both states. This is an interesting finding because youth were generally known to favour more upto- date media, such as social media, as platforms for obtaining information. Finally, the informants’ responses in the interviews also implied that convenience was a significant quality in their preferences, yet each had different definition of the word ‘convenience’, depending on their motives and media use in receiving da’wah.